Does going against the norm on women’s economic participation increase intimate partner violence risk? A cross-sectional, multi-national study - Anaise Williams; Lori Heise; Nancy Perrin; Colleen Stuart; Michele R. Decker (Global Health Research and Policy)
Abstract Background Women’s economic empowerment (WEE) is believed to reduce the risk of intimate partner violence (IPV), yet the relationship between WEE and IPV has proven to be highly variable. Little attention has been given to how the normative WEE environment may influence this relationship across different settings. This study tests whether IPV is associated with Vanguard WEE, defined as individual economic participation that deviates from community norms. Methods This cross-sectional study draws on Demographic and Health Surveys conducted in 44 low- and middle-income countries. The analytic sample was partnered women who participated in the domestic violence module, living in communities with sufficient data to construct WEE norms (n = 186,968). The relationship between Vanguard WEE—measured by the number of WEE activities a woman engaged in that were non-normative in her community—and the incidence of past-year physical IPV, sexual IPV, and partner control was evaluated using a mixed-effects multilevel logistic model. The study also explored interactions between Vanguard WEE and household wealth. Results Women who did not deviate from the community norm had an adjusted probability of 0.15 for experiencing physical IPV in the past year. However, this probability increased to 0.17 (marginal effect (ME): 0.014; 95% CI 0.007,0.021), 0.17 (ME: 0.020; 95% CI 0.010,0.030), and 0.19 (ME: 0.037; 95% CI 0.022,0.051) for women with one, two, and three or more vanguard WEE items, respectively. Physical IPV associated with vanguard WEE was higher among poorer women (p = 0.021). Additionally, the probability of past-year sexual IPV and current partner control increased from 0.05 to 0.08 (p < 0.001) and from 0.38 to 0.44 (p < 0.001), respectively, for women with three or more vanguard WEE items. Conclusions The study provides evidence of partner backlash in the form of IPV among vanguard women—those whose economic activities contradicted local norms. Programs designed to economically empower women in contexts where such participation is non-normative should include mechanisms to monitor and mitigate potential backlash.